Vahdet-i Vücûd Nazariyesinin İzahında Nokta Sembolizmi ve Muhyiddin-i Rûmî’nin Temsîl-i Nokta Adlı Eseri / The Symbolism of the Point (Noqtah) to Expound the Doctrine of the Unity of Being and Muhyiddin al-Rumi’s Work "Tamthil Noqtah" - Yücer, Hür Mahmut (Journal of History Culture and Art Research, 2017)
Abstract The real being in the Islamic thought is only one and it is Allah, the Almighty. All other beings have come to existence through the gradational manifestation (tajalli), condescension (tanazzul) and effusion (tafayyud) of the Transcendental Being (Zat Muta'al). A variety of symbols has been utilised to describe the transition of the being from oneness to plurality, from subtlety (latafa) to grossness (kasafa) and from truth (haqiqa) to metaphor (majaz), In this regard some symbolisms prevail such as of reality and shadow, of seed and tree, of point and letter, The Point (noqtah) is the beginning of the writing (of the word). A book consists of sentences formed by words made up of letters which originate singly from a point. Thus the point constitutes the start and essence of the word and the source of the knowledge. Furthermore, the point is the commencement of the being as well. In other words, it is the initial source and outlet of the universe. It is eventually identical to human being. As essence it is immanent in all beings in addition to forming the beginning. The tradition of defining the being through the symbolism of the point which dates back to Ibn Arabi has been maintained by Ottoman sufi thinkers in the subsequent eras. One of them, Muhyî al-din al-Rumi (d. ca. 946 AH), a sheikh of Khalwatiyya sufi order authored several treatises in which he makes use of abovementioned symbolisms. In the treatise titled Tamthil Noqtah he focuses on the symbolism of the point. In his works he explains the matters by drawing some geometrical shapes such as circles which one in the other, besides speaking of them through prose and poetry. This study firstly deals with the symbolism of the point and then provides an examination of the said work of Muhyî, Tamthil Noqtah, followed by a Turkish transliteration of it. Öz İslam düşüncesine göre gerçek varlık birdir, o da Cenâb-ı Allah’ın kendisidir. Vücûd/varlık, Zât-ı Müteâl’in içerden dışarıya doğru aşama aşama tecelli, tenezzül, tefevvüz etmesi ile oluşmuştur. Varlığın birlikten çokluğa, latiften kesife, hakikatten mecaza geçişini anlatılabilmek için farklı semboller kullanılmıştır. Bu sembollerin başında hakikat ve gölge, tohum ve ağaç, nokta ve harf, hakikat ve ayna, iplik ve halı gibi çeşitli benzetmeler gelmektedir. Nokta, yazının (kelâmın) başlangıcıdır. Noktadan, harf, harften kelime ve isim, kelime ve isimlerden cümle, cümleden kitap oluşmuştur. Bu haliyle nokta kelâmın başlangıcı ve özü, bilginin kaynağıdır. Diğer yandan nokta, kelâm ile eş zamanlı olarak varlığın başlangıcıdır. Evrenin ilk kaynağıdır, ilk çıkış yeridir. En nihâyet nokta insanın ʻaynıdır, hüviyetidir. Fakat bu haliyle o zübde/öz olarak bütün varlığın hem başlangıcı hem de onu içkindir. Varlığı nokta sembolizmi üzerinden tanımlama geleneği İbn Arabî ile başlamış özellikle Osmanlı sûfi düşünürleri tarafından devam etttirilmiştir. Muhyiddin er-Rûmî (946/1539’den sonra) yukarıda bahsedilen sembolleri kullanarak müstakil risâleler kaleme almıştır. Temsîl-i Nokta risâlesi de bunlardan nokta sembolizmine yoğunlaşmıştır. Fakat o eserlerinde sembolün daha iyi anlaşılabilmesi için nesir ve manzum bir yazım tarzı yanında iç içe geçmiş daireler ve şekiller çizerek konuyu anlatma yolunu tutmuştur.